インドヨウ ノ ナンキョク イキ ニ オケル チコウリュウ - 奈須, 敬二; ナス, ケイジ; 永延, 幹男; ナガノブ, ミキオ; Nasu, Keiji; Naganobu, Mikio (1981)
P(論文) 水産庁開洋丸で, 1980年1月13～29日, 100°～120°E間, 61°～65°Sの海域に設定した36点において海洋観測を実施した。1500db面を無流面とする地衡流の計算結果, 概して東向流が卓越していた。時計回りおよび反時計回りの地衡流が105°と110°Eの間に認められた。また時計回りおよび反時計回りの循環流が, 120°E沿いに存在していた。顕著な蛇行流が63°S以南に認められたが, その蛇行流は海底地形の影響を受けているものと考えられる。調査海域内の地衡流の流速は, 64°20'S以北では深さとともに漸次減少しているが, 64°20'S以南では増大している。すなわち, 64°20'S以南の表面流速は0.3cm s^<-1>であったのに対して, 深さ300～400mで最大2.6cm s^<-1>であった。 The research ship KAIYO MARU (Jap. Fish. Agency) occupied 36 oceanographic stations between 61°and 65°S and between 110°and 120°E during the period from January 13 to 29,1980. Dynamic topography and corresponding currents were computed with reference to the 1500-decibar surface. Eastward flow is dominant in the survey area, including the cyclonic and anticyclonic eddies in the area between 62°and 63°20'S and between 105°and 110°E. Cyclonic and anticyclonic circulations are also existing along 120°E. A strong meandering of eastward flow is recognized south of 63°S, which must be influenced by the bottom configuration. The velocity of geostrophic current, relative to the 1500-decibar surface, north of 64°20'S in the survey area gradually decreased toward the deep layer. But it increased south of 64°20'S, giving a maximum of 2.6cm s^<-1> at 300-400m in depth, while the surface velocity is 0.3cm s^<-1>. departmental bulletin paper